2015
DOI: 10.1177/0886260515593544
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Polyvictimization on Delinquency Among Latino Adolescents: A General Strain Theory Perspective

Abstract: Although criminological research has provided support for general strain theory (GST), there is still little known about the relationship between victimization and delinquency among Latino adolescents. This study seeks to fill the gap in the literature by examining the association between a broader measure of victimization (i.e., polyvictimization) and delinquent behavior using data from the Dating Violence Among Latino Adolescents (DAVILA) Study, a national sample of Latino youth. Logistic regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 51 publications
(71 reference statements)
4
41
1
4
Order By: Relevance
“…Therefore, our measure of delinquency is a dummy variable indicating whether each youth had responded “yes” to at least one of these delinquent behaviors. This method is consistent with prior studies using these data (e.g., Cudmore, Cuevas, and Sabina, ).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, our measure of delinquency is a dummy variable indicating whether each youth had responded “yes” to at least one of these delinquent behaviors. This method is consistent with prior studies using these data (e.g., Cudmore, Cuevas, and Sabina, ).…”
Section: Methodssupporting
confidence: 90%
“…Information about a youth's demographic information was obtained through his or her caregiver. More information about the study's aims, methodology, and major findings can be found in Sabina and Cuevas (2013) and Cudmore, Cuevas, and Sabina (2017).…”
Section: Samplementioning
confidence: 99%
“…Yet, although normalized, youth in this study were also negatively affected and traumatized by experiences of violence within their homes and communities. A growing body of literature strongly indicates the negative effects of multiple exposure to violence in homes and communities (Cudmore, Cuevas, & Sabina, 2015; Cyr et al, 2013; Elsaesser & Voisin, 2015; Voisin & Elsaesser, 2013). Violent victimization and exposure to violence are associated with a variety of mental health concerns in youth including anxiety, depression, PTSD, and aggression (Ford et al, 2010; Hartinger-Saunders et al, 2011; Ng-Mak et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual, physical, emotional abuse and neglect, or multiple types of maltreatment (Nguyen, Dunne, & Le, 2010) have been linked to low self-esteem (Nguyen et al, 2010), depression, anxiety (Afifi et al, 2014; Chapman et al, 2004; Edwards, Holden, Felitti, & Anda, 2003; MacMillan et al, 2001; Mills et al, 2013; Nguyen et al, 2010; Spataro, Mullen, Burgess, Wells, & Moss, 2004; Springer, Sheridan, Kuo, & Carnes, 2007), suicidal ideations and/or attempts (Afifi et al, 2014; Hadland et al, 2015; Marshall, Galea, Wood, & Kerr, 2013). Similarly, childhood maltreatment may lead to delinquent behaviour (Cudmore, Cuevas, & Sabina, 2015; Gao, Wong, & Yu, 2016) or externalizing problems (Mills et al, 2013; Spataro et al, 2004) often involving problematic substance use (Markowitz et al, 2011; Ompad et al, 2005). Exposure to childhood maltreatment has also been associated with impaired cognitive development (Mills et al, 2011), a range of physical health disorders (Wegman & Stetler, 2009) as well as poor adherence to medications (Markowitz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%